Sobre o conceito de técnica em Jürgen Habermas: traços de uma filosofia da tecnologia - Silva, Maurício Fernandes da (Universidade do Vale do Rio dos Sinos, 2018)
Technosciences reached an important position in contemporary society marked mainly by the expressive advances in the fields of biotechnology and genetic engineering, which marked significantly the intellectual environment of the late twentieth century. The question of technique has played an important role in Habermas's work since his early essays in the 1960s, through his opus magnum in the 1980s and his most recent writings, presenting himself as a lively and recurrent dialogical thematic axis in the architectonic of the thought of such philosopher. We can see an evolution of Habermas's thinking about the technological phenomenon, a growing interest in such phenomenon since his critique of the proposals of Herbert Marcuse and other members of the Frankfurt School in the 1960s until his critique of the impacts of biotechnical interventions on horizon of our Self-Understanding Ethics of the Species in 2001 and 2014. However, even with an explicit resumption of the question of technique in his thinking, Habermas does not appear in the debates in Philosophy of Technology, nor does appear as a referential author in this context. In this research, we will focus on the theoretical-conceptual development on the technical phenomenon in Habermas' thought, thematizing the existence of a Philosophy of Technology in his intellectual trajectory. In this sense, we will argue the existence of a continuity line between the first writings of Habermas and his most recent criticism, which will reveal to us a Philosophy of the Technique that thinks this phenomenon in important marks of century XX and beginnings of the current century. The problem that directs us in this research is a forgetfulness of this aspect of the Habermas thought in the field of the debates in Philosophy of the Technique. Thus, we seek beyond thematize the existence of a Philosophy of technology, pointing to the contributions of his thought to the current debates in Philosophy of Technology and bioethics.
Keywords: Filosofia da técnica; Tese da colonização; Natureza humana; Biotécnica; Ética da espécie; Philosophy of technique; Colonization thesis; Human nature; Biotechnology; Ethics of the species; ACCNPQ::Ciências Humanas::Filosofia